Study the Impact of the waste which discharged from Al-Karama and Sharq- Dijla water treatment plants in water pollution of Tigris River water - H.G.Q.AL-Amier, Faisal; F. AL-Fatlawy, Yarub; A. Rasheed, Khalid. (Iraqi Journal of Science, 2023)
This study was conducted to evaluate the effect of discharge of water purification plants ,on the purity of Tigris River water in Baghdad city. The two studied plants were involved in the study : Sharq –Dijla and Al-Karama water purification plants. The study was attempted to focus on probable pollutants. Chemical, physical tests were accomplished on water samples collected from four sites with fact of three replicates for each sample of each site of the river and the plant : before, after, inside the plants and at the pipe. This study started from October 2012 to September 2013. In case of heavy metals Results showed that the highest level of aluminum was 1.08 ppm during (December-January) at Sharq-Dijla plants, while the lowest level was 0.059 ppm during (August- September) at AL- Karama plants ,while results of iron which recorded the highest level 3.30 ppm during (December-January) at Sharq –Dijla plants, while the lowest level was 1.63 ppm during (August- September) at Sharq –Dijla plants. It was found that the highest level of turbidity was 119 N.T.U during (December-January) at Sharq- Dijla plants, while the lowest level was 33.0 N.T.U during ( June-July) at Sharq-Dijla plants. While the highest level of EC was 1068 μS/cm during (December-January) at Sharq-Dijla plants, while the lowest level was 693 μS/cm during ( June-July) at Sharq-Dijla plants .T.D.S recorded highest level during (December-January) at AL- Karama plants which was 687 ppm , while the lowest recorded level was 506 ppm during ( August- September) at Sharq-Dijla plants, also the highest level of T.S.S was 793 ppm during (December-January) at AL- Karama plants, while the lowest level was 410 ppm during ( August- September) at Sharq-Dijla plants .